2011
DOI: 10.2298/abs1104117c
|View full text |Cite
|
Sign up to set email alerts
|

Mosses as biomonitors for radioactivity following the Chernobyl accident

Abstract: In this work 137Cs and 40K radionuclide concentrations in moss collected at NP Djerdap in the period from 1996 to 2009 are presented. Values of the substrate-moss transfer factor for 137Cs and 40K were calculated. The effective and biological half-life of 137Cs in Homalothecium sericeum moss collected in the period from 1996 to 2008 on the archeological locality of Lepenski Vir was also calculated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…( 2.3) and (2.2), respectively, are reported in table 2 and shown in figure 5, together with its physical halflife (t 1/2 ), for all investigated samples. Our values are in good agreement with the literature [13,14], where the cesium biological half-life in different moss species is lower than ten years. Reported values of biological half-life for the different species collected are in good agreement with the activity concentration results (see table 2 and figure 4).…”
Section: Resultssupporting
confidence: 91%
“…( 2.3) and (2.2), respectively, are reported in table 2 and shown in figure 5, together with its physical halflife (t 1/2 ), for all investigated samples. Our values are in good agreement with the literature [13,14], where the cesium biological half-life in different moss species is lower than ten years. Reported values of biological half-life for the different species collected are in good agreement with the activity concentration results (see table 2 and figure 4).…”
Section: Resultssupporting
confidence: 91%
“…Except for the high 137 Cs uptake in Bryum , activity seemed to be determined predominantly by the substrate. A previous study in Serbia [ 23 ] found substrate to moss ratios of 0.27 to 0.92, but did not identify parameters controlling Cs availability. In the Chornobyl area, pond sediments in shallow waters exhibited the highest 137 Cs concentrations at the very surface [ 14 ], and the very same situation can be assumed for sediments, which have become dry only recently.…”
Section: Resultsmentioning
confidence: 88%
“…In midlatitudes, the 7 Be's seasonal variations show a maximum in summer and a minimum in winter and it is certainly one of the radionuclides regularly taken by mosses (15)(16)(17)(18). Although extensive research on radionuclides in air and bioindicators due to the contamination from nuclear probes and reactor breakdowns is available, there are limited data on natural radionuclides content in air or mosses especially for rural areas (19)(20)(21)(22)(23). The purpose of this paper is to present activity concentrations of natural radionuclides in different moss species collected at the territory of eastern Serbia in the period 2008-2013. .…”
mentioning
confidence: 99%